A mesoporous encapsulated nanozyme for decontaminating two kinds of wastewater and avoiding secondary pollution. Issue 27 (3rd July 2020) - Wang, Faming; Zhang, Yan; Liu, Zhengwei; Ren, Jinsong; Qu, Xiaogang
Abstract : A complex nanozyme with dual enzyme mimic activities has been constructed by confining Au/Pt/Co tri-metal in a macroporous silica scaffold. The nanozyme has a huge advantage in treating different sewages in one system. Abstract : Water pollution is becoming a major and serious issue all over the world. However, considering conventional methods for wastewater purification is chemically, energetically and technologically intensive, thus finding a reliable and energy-saving method is still a considerable conundrum. Herein, a mesoporous encapsulated dual-function complex nanozyme consisting of gold, platinum, and cobalt tri-metal is reported, and it not only shows high activity for water purification but also has outstanding resistance to the harsh conditions of the wastewater. This complex nanozyme simultaneously exhibits excellent peroxidase mimicking activity and catalase mimicking activity, which could handle two kinds of wastewater effectively in one system, thus avoiding the use of fresh H2 O2 resources and greatly saving resources. In comparison with conventional methods, this nanozyme integrated the "oxidation" process and the "deoxidation" process together in one system very well, successfully avoiding the problem of secondary pollution in the current methods. Furthermore, the treated water is compatible with cells and safe for mice. Therefore, this highly-active nanozyme provides a resource-saving and environment-friendly method for wastewater decontamination, which will be a potential way to directly convert polluted water into bio-safe resources in the future.